2016
DOI: 10.3847/2041-8205/817/1/l3
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of High-Altitude Open Clusters in the Milky Way

Abstract: We present a dynamical study of the effect of the bar and spiral arms on the simulated orbits of open clusters in the Galaxy. Specifically, this work is devoted to the puzzling presence of high-altitude open clusters in the Galaxy. For this purpose we employ a very detailed observationally motivated potential model for the Milky Way and a careful set of initial conditions representing the newly born open clusters in the thin disk. We find that the spiral arms are able to raise an important percentage of open c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Thus, our approach may have an impact on the identification of dynamical signatures of resonant orbits and on the degree of chaos in the solar neighbourhood, and on its local phase-space structure (Chakrabarty 2007;Chakrabarty & Sideris 2008). It may also shed light on the origin of kinematic moving groups, believed to be related to resonances (Antoja et al 2008(Antoja et al , 2009(Antoja et al , 2011Moreno et al 2015;Martinez-Medina et al 2016). These topics, as well as a dynamical analysis of three-dimensional potentials, will be the subject of a forthcoming study.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, our approach may have an impact on the identification of dynamical signatures of resonant orbits and on the degree of chaos in the solar neighbourhood, and on its local phase-space structure (Chakrabarty 2007;Chakrabarty & Sideris 2008). It may also shed light on the origin of kinematic moving groups, believed to be related to resonances (Antoja et al 2008(Antoja et al , 2009(Antoja et al , 2011Moreno et al 2015;Martinez-Medina et al 2016). These topics, as well as a dynamical analysis of three-dimensional potentials, will be the subject of a forthcoming study.…”
Section: Discussionmentioning
confidence: 93%
“…Numerical simulations of open cluster orbital evolution have shown that it is possible for the spiral arms of the Galaxy to have a large vertical effect on clusters, giving them large out-of-plane excursions (>200 pc), though these orbits tend to be chaotic (see e.g., Martinez-Medina et al 2016). Martinez-Medina et al (2017) investigated the survival of such high-altitude open clusters, and find that clusters in the plane of the disk and clusters with relatively large vertical motions (z max 3.5 kpc) tend to have the longest lifetimes.…”
Section: Orbitmentioning
confidence: 99%
“…It is therefore surprising to find Gaia 1 in its present orbit at the present day. This suggests that either it has recently moved into this orbit, perhaps after an interaction with a spiral arm (Martinez-Medina et al 2016), or that it has experienced significant mass loss in the past, and is now on the verge of complete destruction. Significant mass loss in the past would tend to support the association of the extratidal stars we find with radial velocities, metallicities and photometry consistent with Gaia 1.…”
Section: Orbitmentioning
confidence: 99%
“…In a previous work (Martinez-Medina et al 2016a), we showed that a mechanism able to lift open clusters way up the Galactic plane are the spiral arms. The presence of the spiral arms induces several clusters to be violently lifted from the Galactic plane, to heights up to 3 kpc.…”
Section: Survival Of Lifted Clustersmentioning
confidence: 91%
“…In Figure 6 we show the mass evolution, as well as the orbits, for three examples of lifted clusters from the work by Martinez-Medina et al (2016a). The blue lines indicate the life stage of the cluster when it moves confined to the Galactic plane; the red lines indicate the second part of its evolution: when the cluster oscillations take it away from the plane, crossing the disk.…”
Section: Survival Of Lifted Clustersmentioning
confidence: 99%